Changes in suicide and non‐suicidal self‐injury ideation and the moderating role of specific emotions over the course of dialectical behavior therapy. Issue 3 (24th September 2020) - Rizvi, Shireen L.; Fitzpatrick, Skye
Abstract: Objective: Dialectical behavior therapy (DBT) targets suicidal behavior and non‐suicidal self‐injury (NSSI) as well as urges/ideation to engage in these behaviors. However, it remains unclear which specific suicidal ideation (SI) and NSSI ideation domains (i.e., frequency, worst intensity, average intensity, perceived likelihood of future ideation, and duration of ideation), if any, are impacted, and whether specific emotions moderate these effects. Method: 73 individuals with borderline personality disorder (BPD), enrolled in six months of DBT, completed interviews of suicide and NSSI ideation and self‐report measures of specific emotions at baseline, mid‐treatment, and post‐treatment. Results: Generalized estimation equations revealed that all domains of suicidal ideation decreased over the course of DBT, but for NSSI domains, only ideation intensity decreased. Higher levels of shame/guilt predicted less, and higher fear predicted more, reduction in SI and NSSI ideation frequency. Higher shame/guilt also predicted more reduction in worst SI intensity. Higher sadness predicted greater reductions in SI intensity and duration, but less reductions in the perceived likelihood of future NSSI ideation. Conclusions: These findings suggest that DBT effectively reduces several facets of SI, but more work is required to target NSSI ideation. Results also suggest that targeting shame/guilt may be important to reducing SI and NSSI ideation.